The selective bleed variable cycle engine - Nascimento, M. A. R. (Cranfield University, 1992)
A new concept in aircraft propulsion is described in this work. In particular, variable jet engine is investigated for supersonic ASTOVL aircraft. This engine is a Selective Bleed Variable Cycle, twin shaft turbofan. At low flight speeds the engine operates as a medium bypass turbofan. At supersonic cruise it operates as low bypass turbofan without reheat. The performance of the engine and its components is analyzed using a novel matching procedure. Off-design engine performance characteristics are explained, compressor running lines are shown, and variable geometry requirements are described. The performance analysis shows that fuel savings are significant, thus reducing aircraft take-off weight. The major advantage of this engine is that all the components are used continuously for all operating modes, thus incurring low weight penalties. The benefits predicted by this preliminary investigation indicate that further research on this engine should be carried out. The matching procedure developed and described shows itself to be very effective for two-shaft engines with a fixed geometry LP turbine. The method can also be extended to three shaft cases with or without a variable geometry LP turbine. Extensive development of compressor and turbine design and performance software has been undertaken.